New business strategy to improve the enterprise resources planning (erp) system in order to increase the performance and efficiency of the operational maintenance program: case of chevron indonesia - Kresno Adikusumo, Linung; Dung Do, Anh (The Indonesian Journal of Business Administration, 2016)
Abstractâ€” Since last year the oil and gas industry in grim conditions. Almost all companies in difficult conditions as a result of oil and gas prices were low. Even today a giant oil companies like Exxon, Chevron, Shell and others also began to be affected. Chevron, the current was devastated because the company is focused on upstream business where oil reserves are available today are secondary and tertiary reserves. Investment in the exploration of oil and gas reserves of the secondary and tertiary very expensive because it requires a modern and sophisticated technology. Unsuccessful drilling activity will result in tremendous losses in some oil and gas fields. External factors also affect the company in how to run a business; local government permits, issue a contract extension, the discovery of shale gas, and global economic conditions greatly affect the company to make the best strategy. These conditions forced the company to reduce exploration activities and focus more on production. Production is the most economical series in the upstream business chain. Crude oil is a commodity, the competition occurs in differentiating the company to improve the effectiveness and efficiency of the business. Companies must also adhere to the existing rules so as to build the confidence of the shareholders. Efficiency through the development of organizations that are into is a must, if not then Chevron would not survive in competition with rivals. To create a sustainable competitive advantage, Chevron should remain sustainably strengthen the factor that differentiates it from its competitors. Technology as a differentiator to be able to enhance the company's core competencies, thus making a positive impact on the company's core business. ERP (Enterprise Resource Planning) system is essential to be able to be a tool that is capable of integrating the functions of important business. Module EAM (Enterprise Asset Management) is part of the ERP system and as part closest to the Operation Maintenance and should be able to support the maintenance business in order to achieve better business efficiency and effectiveness through increased system reliability, capability (usability and functionality) and sophisticated reporting system. In other words, implementation of ERP systems In other words, implementation of ERP systems and specifically to the EAM module will be able to optimize production by reducing the LPO (Lost Production Opportunity). Proposal business strategies to increase investment in ERP are: 1. Revision JDE governance in Indo Asia Business Unit and IT support Team, 2. Build a Business Intelligence as a solution for reporting requirements, 3. Realize the JDE upgrade project to improve the reliability and capabilities of the system, 4. Implement Viziya to strengthen the maintenance scheduling system, 5. Conduct regular visits to customers, holding gatherings for Power Users, and training regularly. Some of the proposed strategies have been approved by the management of Chevron Indonesia, while several other strategies are still in the approval process. The new business strategy will strengthen the ERP system particularly EAM module to improve the performance and efficiency of program maintenance operations and strengthen core competencies and create a sustainable competitive advantage.Â Keywords: Enterprise Resources Planning, Enterprise Asset Management, Business Strategy Introduction